Are we comparing frontotemporal dementia and Alzheimer disease patients with the right measures?. (15th April 2016) - Deutsch, Mariel B.; Liang, Li-Jung; Jimenez, Elvira E.; Mather, Michelle J.; Mendez, Mario F.
ABSTRACT: Background: Clinical research studies of behavioral variant frontotemporal dementia (bvFTD) often use Alzheimer disease (AD) as a comparison group for control of dementia variables, using tests of cognitive function to match the groups. These two dementia syndromes, however, are very different in clinical manifestations, and the comparable severity of these dementias may not be reflected by commonly used cognitive scales such as the Mini-Mental State Examination (MMSE). Methods: We evaluated different measures of dementia severity and symptoms among 20 people with bvFTD compared to 24 with early-onset AD. Results: Despite similar ages, disease-duration, education, and cognitive performance on two tests of cognitive function, the MMSE and the Montreal Cognitive Assessment (MoCA), the bvFTD participants, compared to the AD participants, were significantly more impaired on other measures of disease severity, including function (Functional Assessment Questionnaire (FAQ)), neuropsychiatric symptoms (Neuropsychiatric Inventory (NPI)), and global dementia stage (Clinical Dementia Rating Scales (CDRs)). However, when we adjusted for the frontotemporal lobar degeneration-CDR (FTLD-CDR) in the analyses, the two dementia groups were comparable across all measures despite significant differences on the cognitive scales. Conclusion: We found tests of cognitive functions (MMSE and MoCA) to be insufficient measures for ensuring comparability between bvFTD and AD groups. In clinical studies, the FTLD-CDR, which includes additional language and behavior items, may be a better overall way to match bvFTD and AD groups on dementia severity.